Organocatalytic route for the synthesis of propionylated starch. (10th February 2016) - Di Filippo, S.; Tupa, M.V.; Vázquez, A.; Foresti, M.L.
Highlights: Propionylated starches can deliver specific SCFAs to the colon. A non-conventional organocatalytic route for propionylation of starch is proposed. Propionylated starch with the clinically required DS can be obtained within 2–3 h. For increasing DS values a progressive loss of granules crystallinity is observed. Reduction of crystallinity induces higher susceptibility to chemical modification. Abstract: In recent years acetylated, propionylated and butyrylated starches have received special attention due to their capacity to deliver specific short chain fatty acids (SCFAs) to the colon in a sustained and predictable manner, and thus contribute to maintaining the normal physiologic function of the large bowel and preventing specific diseases. In the current contribution a non-conventional organocatalytic solventless route for the eco-friendly propionylation of corn starch is proposed. The catalyst used in the acylation is a naturally occurring α-hydroxy acid (l -tartaric acid). Propionylated starches with degree of substitution (DS) in the 0.05–1.59 interval were obtained and characterized in terms of chemical structure, morphology, crystallinity, thermal stability and hydrophilicity. Results showed that by the proposed methodology propionylated starch with the DS required for clinical use (i.e. 0.2–0.3) could be obtained within 2–3 h of reaction. Characterization results evidenced the progressive loss of crystallinity of starch granules as higher substitution levels were conferred.